(Re)call and Response: Organizing with Community-University Talks - Hampton, Rosalind; Conway, Cora-Lee (Canadian Journal of Higher Education / Revue canadienne d'enseignement supérieur, 2022)
This article documents and analyses Black student-led organizing by Community-University Talks, a collective of academics and local community members who organized together between 2012 and 2017 in Montreal. The co-authors of this article founded Community-University Talks in December 2011, as Black women who had just begun doctoral studies in Educational Studies at McGill University. Now, a decade later, they recall and respond to this experience through narrative inquiry involving collaborative remembering, writing, and dialogue. This study is further guided by a critical engagement with the material culture of the Community-University Talks archive, which includes notes and correspondences, minutes from meetings, reports, event posters, memorabilia,photographs, and video footage.